The Use of Jargon Among Anime Lovers on the Cleansound Studio YouTube Channel: A Sociolinguistic Study - Dhida Meilando Cahyo Rio Utomo; Yunita Suryani; I Wayan Letreng (ETNOLINGUAL, 2026)
Jargon emerges from the interactions of people in communities with similar interests that create unique vocabulary within them. This study focuses on the analysis of the use of jargon in the anime community through interactions on the Cleansound Studio YouTube channel. Through qualitative descriptive methods, data is mined to find the meaning of speech with non-numerical properties. Data collection techniques use passive listening and transcription, namely the technique of listening without direct involvement in it, understanding what is said and then converting it into written form. Digital observation is carried out to find videos that match the main topic of the study. Data is understood repeatedly and arranged according to its group, namely classification based on language origin consisting of three languages: (1) Indonesian, (2) English, and (3) Japanese, as well as classification based on slang including language merging and changes in meaning from the original. The results of the study show that English is more dominant in anime lover jargon because its status as an international language which ultimately influences the terms including in Indonesia and Japan. Despite this, Japanese isn't significantly behind English. This is because anime fans' culture follows its origins, namely Japan, and so the use of terms inherent in anime has also been carried over into the community. The group's need to convey information concisely fosters linguistic creativity, leading to the creation of slang.